Screening tools interventions and strategies for early identification and management of autism spectrum disorders - Alzamzami, Abdulghani Abdulaziz; Binsalamah, Ibrahim Mohammed; Alharbi, Ahmed Ghazi Shadad; Almousa, Abdulmajeed Mesfer; Algaidi, Marwan Talal; Alsultan, Khaled Mohammed; Alshatti, Qanot N.; Tuwaymah, Ali Mohammed Abu; Alruwaili, Waleed Owaid; Alajmy, Maryem S.; Alabdulmohsen, Ruba Hashim (International Journal Of Community Medicine And Public Health, 2023)
Autism spectrum disorder is a neurodevelopmental disorder marked by social communication difficulties, restricted interests, and repetitive activities. Both genetic and environmental variables impacting the growing brain influence it. Around the world, 1 in 100 children is identified with autism spectrum disorder. Estimates of prevalence have increased over time and varied significantly inside and across sociodemographic groups. Autism spectrum disorder is a prevalent neurodevelopmental condition that significantly shortens life expectancy. Early diagnosis on a community level is a critical public health concern since mounting evidence shows that early diagnosis makes functional gains and has better outcomes. In healthcare settings, autism spectrum disorder screening tools can be utilized to precisely confirm the diagnosis of autism. The American Academy of Pediatrics recommends screening for ASDs between ages 18 and 24 months, although recent research indicates that abnormal behaviours may be visible in certain children even earlier. the checklist for autism in toddlers, the modified checklist for autism in toddlers, the psychological development questionnaire-1, and the autism behaviour checklist are some of the commonly used screening tools in practice for the diagnosis of autism spectrum disorder. The majority of interventions are non-pharmacological and depend on behavioural modification strategies. Pharmacological therapy should only be used to treat target symptoms that are resistant to behavioural treatment. Although there is no cure, prompt and suitable intervention can dramatically raise the quality of life for children. The purpose of this research is to review the screening tools, interventions, and strategies for early identification and management of autism spectrum disorder.